The relationship between heart rate deceleration during encoding and subsequent sleep dependent emotional memory consolidation - Smith, Caitlin J (Department of Psychology, 2026)
Emotion and sleep are known to enhance memory, both at encoding and during the consolidation process. Furthermore, those with posttraumatic symptoms have sleep and emotional memory disruption. The interaction of emotion and sleep on subsequent recall is unclear in such a sample. This study examined the relationship between heart rate deceleration (HRD), a physiological autonomic nervous system (ANS) measure of emotion, at encoding, and subsequent sleep-dependent emotional memory consolidation. The study, based on archival data, recruited female participants, living in low-income South Africa characterised by persistent exposure to crime and violence: those with posttraumatic stress disorder (PTSD; n = 21), trauma-exposed (TE; n = 19), and healthy controls (HC; n = 20). Participants viewed highly-arousing positive or negative images and low-arousing neutral images. HRD was measured during picture presentation. Participants spent an 8-hour interval of either nocturnal sleep or daytime waking, before completing a memory recognition task to identify previously viewed images in contrast to new images. Results showed no significant differences in HRD at encoding between negative or positively valenced and neutral information, irrespective of between-group differences (HC, TE or PTSD) or condition (sleep or waking). Regarding the relationship between HRD recorded during encoding and performance on the subsequent memory task, there was an association between HRD and recall for positively valenced information rather than negative and neutral information. This association existed for those in the sleep but not the waking condition. The results suggest that psychophysiological reactivity at encoding promotes the consolidation of positive information during sleep, which may be a protective factor for this female cohort, living in an environment dominated by a high degree of negative stimuli in the form of persistent violence and crime. With regards to the group- specific associations between HRD and subsequent recognition of valenced material, there were no significant correlations in the PTSD group. TE participants had greater psychophysiological reactivity associated with better memory recognition accuracy across intervals of sleep and waking for both valenced and neutral stimuli, with some inconsistencies across sleep and wake conditions. HCs demonstrated better memory recognition with less psychophysiological reactivity for neutral information after sleep. The results tentatively suggested that in participants with PTSD, no association between HRD at encoding and memory outcomes is indicative of ANS dysregulation. In TE participants, the finding suggests that autonomic activity plays a key role in promoting memory formation, although indiscriminately of valence or sleep/waking state. In HCs, the result suggests that low physiological reactivity at encoding is necessary for remembering neutral information in those free from trauma. Concerning rapid eye movement (REM) sleep, TE participants showed this association, and there was also an association that indicated that as REM percentage increased, memory recognition accuracy for negative stimuli decreased. The results indicated a trend suggesting that as REM fragments, memory recognition accuracy for neutral stimuli decreases. These findings suggest that REM may be important for ensuring that there is a reasonable distribution of neutral and negative memory traces upon awakening, promoting resilience in the recovery from trauma. The research highlights that the relationship between HRD at encoding and subsequent memory performance is complex and requires further investigation. Future research should compare those living in high and low socio-economic contexts and control for the daily exposure to negative, positive and neutral stimuli in the environment, to better understand how both emotion and sleep contribute to memory processing.